Identification of anti-Gram-negative bacteria agents targeting the interaction between ribosomal proteins L12 and L10 - Weiwei Wang; Chao Liu; Ningyu Zhu; Yuan Lin; Jiandong Jiang; Yanchang Wang; Yan Li; Shuyi Si (Elsevier, 2018)
Gram-negative bacteria have become the main pathogens and cause serious clinical problems with increased morbidity and mortality. However, the slow discovery of new antimicrobial agents is unable to meet the need for the treatment of bacterial infections caused by drug-resistant strains. The interaction of L12 and L10 is essential for ribosomal function and protein synthesis. In this study, a yeast two-hybrid system was established to successfully detect the interaction between L12 and L10 proteins from gram-negative bacteria Escherichia coli, which allows us to screen compounds that specifically disrupt this interaction. With this system, we identified two compounds IMB-84 and IMB-87 that block L12−L10 interaction and show bactericidal activity against E. coli. We used glutathione-S-transferase (GST) pull-down and surface plasmon resonance (SPR) assays to demonstrate that these compounds disrupt L12−L10 interaction in vitro and the target of compounds was further confirmed by the overexpression of target proteins. Moreover, protein synthesis and elongation factor G-dependent GTPase activities are inhibited by two compounds. Therefore, we have identified two antibacterial agents that disrupt L12−L10 interaction by using yeast two-hybrid system. KEY WORDS: Yeast two-hybrid, Escherichia coli, Ribosome, L12/L10, Antimicrobial agents